(untitled) (Analysis in Theory and Applications, 2018)
In the present paper, we deal with Chlodowsky type generalization of the Baskakov operators, special case of these operators includes Chlodowsky type Meyer– König and Zeller operators (see [21]). With the help of Bohman-Korovkin theorem, we obtain some approximation properties for these operators. We give a modification of the operators in the space of differentiable functions and we also present examples of graphs for approximation. Finally, we apply these operators to the solution of the differential equation.